Method for producing aluminum oxide and gallium chloride from fly ash
By mixing fly ash with a roasting agent, and using the separation process of hydrochloric acid solution and adsorption resin, the problem of high extraction cost of aluminum and gallium in fly ash is solved, and the extraction of high-purity alumina and gallium chloride is achieved, reducing the reduction of Production costs and simplify process flow.
Patent Information
- Application Number
- CN202411336153.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-24
AI Technical Summary
In the prior art, the cost of extracting aluminum and gallium from fly ash is relatively high and it is difficult to effectively reduce.
Fly ash and roasting agent are mixed with roasting agent, and multiple decomposition and adsorption resin separation are used to perform multiple decomposition removal and adsorption resin separation. High-purity alumina and gallium chloride are obtained through crystallization and washing processes, and the recycling of hydrogen chloride gas is used to reduce production. cost.
The efficient extraction of high-purity alumina and gallium chloride from fly ash is achieved, reducing production costs, simplifying the process flow, reducing the removal steps of silicon oxide, and improving the purity of aluminum and gallium yield.
Smart Images

Figure CN119176579A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal extraction, in particular to a method for producing aluminum oxide and gallium chloride from fly ash. Background Art
[0002] Fly ash from pulverized coal furnaces is a type of solid waste emitted by coal-fired power plants. With the rapid development of the electric power industry, its emissions are increasing day by day. The stacking and storage of fly ash not only requires the occupation of large tracts of land, but also harms the environment. Therefore, vigorously developing and utilizing the potential application value of fly ash from pulverized coal furnaces, turning waste into treasure and harm into benefit has become an important technical and economic policy in my country's economic construction.
[0003] At present, the fly ash from pulverized coal furnaces in my country is about 9 times that of circulating fluidized bed fly ash. Compared with circulating fluidized bed fly ash, it is more difficult to extract alumina from pulverized coal furnace fly ash. Pulverized coal furnace fly ash is formed by rapid cooling of coal after high-temperature combustion (1300-1400℃). The alumina-silicon glass phase maintains a metastable structure of high-temperature liquid structure arrangement. Therefore, pulverized coal furnace fly ash has high chemical stability, which makes the alumina and silica contained in pulverized coal furnace fly ash less active and difficult to dissolve directly. It needs to be activated for effective extraction. At present, the methods for extracting aluminum and gallium from pulverized coal furnace fly ash include sulfate roasting, sulfuric acid leaching, alkali dissolution, etc. However, the production cost of extracting aluminum and gallium using the above methods is relatively high. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for producing aluminum oxide and gallium chloride from fly ash, so as to solve the problem of high cost of extracting aluminum and gallium from fly ash in the prior art.
[0005] In order to achieve the above-mentioned object, according to one aspect of the present invention, there is provided a method for producing aluminum oxide and gallium chloride from fly ash, the method comprising: a) mixing fly ash with a calcining agent to obtain a solid phase material; calcining the solid phase material to obtain clinker; b) soaking the clinker in a first hydrochloric acid solution, separating the solid and the liquid, and obtaining the impurity-removed clinker; soaking the impurity-removed clinker in a second hydrochloric acid solution, separating the solid and the liquid, and obtaining a dissolving solution; c) adsorbing the dissolving solution through a resin to obtain an effluent and an adsorption resin, wherein the effluent is aluminum chloride; d) washing the adsorption resin with a third hydrochloric acid to obtain gallium chloride; e) crystallizing the effluent to obtain aluminum chloride hexahydrate crystals; and calcining the aluminum chloride hexahydrate crystals to obtain aluminum oxide and hydrogen chloride gas.
[0006] Further, in a), the calcining agent includes CaCl2·2H2O; preferably, the mass ratio of fly ash to calcining agent is 0.3-2:1, more preferably 0.8-1.2:1; preferably, the calcining temperature of the solid phase material is 600-1200°C, more preferably 900-1100°C; preferably, the calcining time of the solid phase material is 1.5-5h, more preferably 3-4h.
[0007] Further, in b), the mass content of the first hydrochloric acid solution is 0.2% to 30%, preferably 0.5% to 5.0%; preferably, the volume mass ratio of the first hydrochloric acid solution to the clinker is 3 to 10 mL: 1 g, more preferably 4 to 6 mL: 1 g; preferably, the soaking time of the clinker is 0.5 to 3 h, more preferably 1 to 2 h.
[0008] Further, in b), the mass content of the second hydrochloric acid is 15% to 31%, preferably 20% to 29%; preferably, the volume mass ratio of the second hydrochloric acid solution to the clinker after impurities are removed is 3 to 8 mL: 1 g, more preferably 4 to 5 mL: 1 g; preferably, the time for soaking the clinker after impurities are removed is 0.5 to 5 h, more preferably 1 to 2 h; preferably, the temperature for soaking the clinker after impurities are removed is 40 to 160°C, more preferably 50 to 70°C.
[0009] Further, in c), the resin comprises a quaternary ammonium anion exchange resin; preferably, the flow rate of the eluate in the resin is 1.5 to 5.0 BV / h, more preferably 2.0 to 3.5 BV / h; preferably, the iron ion concentration in the eluate is 200 to 320 g / L, more preferably 250 to 300 g / L.
[0010] Further, in d), the mass content of the third hydrochloric acid is 0.5%-5%; preferably, after washing the adsorption resin with the third hydrochloric acid, sodium hydroxide is added to the eluate, and a gallium-rich solution is obtained after filtration, and a fourth hydrochloric acid solution is added to adjust the pH to obtain gallium chloride; preferably, the added sodium hydroxide is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 3-8 mol / L, more preferably 5-6 mol / L; preferably, after adding sodium hydroxide, it is maintained for 0.5-4h to obtain a gallium-rich solution, more preferably 1-2h; preferably, the temperature after adding sodium hydroxide is 40-90°C, more preferably 60-80°C; preferably, the pH is adjusted to 1-3 to obtain gallium chloride, more preferably 1.8-2.2.
[0011] Further, in e), crystallization includes evaporative crystallization; preferably, the temperature of evaporative crystallization is 105-150°C, more preferably 110-120°C; preferably, the roasting temperature of aluminum chloride hexahydrate crystals is 900-1150°C, more preferably 1000-1050°C; preferably, the roasting time of aluminum chloride hexahydrate crystals is 2-5h, more preferably 2.5-3h.
[0012] Furthermore, in d), after adding the fourth hydrochloric acid solution to adjust the pH, an organic extractant is added for extraction and liquid separation to obtain an organic phase; and the organic phase is back-extracted and liquid separated using an aqueous back-extractant to obtain gallium chloride.
[0013] Furthermore, the organic extractant includes an extractant and a diluent, the extractant includes tributyl phosphate and di(2-ethylhexyl)phosphoric acid, and the diluent includes sulfonated kerosene; the volume ratio of tributyl phosphate to di(2-ethylhexyl)phosphoric acid is 1 to 6:1, preferably 2 to 3:1; the volume ratio of the extractant to the diluent is 0.5 to 2:1; preferably, the extraction temperature is 20 to 30°C; preferably, the extraction time is 10 to 60 minutes.
[0014] Furthermore, before stripping, the organic phase is washed with a fifth hydrochloric acid solution, the mass content of the fifth hydrochloric acid solution is 25%-36%, preferably 30%-36%; preferably, the volume ratio of the fifth hydrochloric acid to the organic phase is 2:1; preferably, the washing time of the fifth hydrochloric acid solution is 10 to 30 minutes; preferably, the aqueous back-extracting agent includes a sixth hydrochloric acid solution, the mass content of the sixth hydrochloric acid solution is 0.8%-5%, more preferably 1%-3%; preferably, the stripping temperature is 20 to 30°C; preferably, the stripping time is 10 to 60 minutes, more preferably 20 to 30 minutes; preferably, after stripping with an aqueous back-extracting agent, the stripping is concentrated and then separated to obtain gallium chloride.
[0015] By applying the technical solution of the present invention and the above method, the calcining agent and fly ash are first roasted to obtain activated clinker, and the raw materials are repeatedly impurized with hydrochloric acid solution to obtain aluminum chloride hexahydrate crystals that are easy to crystallize and have high purity, thereby obtaining aluminum oxide and gallium chloride with high purity, reducing the cost of the purification process. In addition, hydrogen chloride gas is generated during the preparation process, realizing the recycling of hydrochloric acid solution and reducing the cost of raw materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 The reaction flow chart according to Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0019] As mentioned in the background technology, the cost of recovering aluminum and gallium from fly ash is relatively high in the prior art. Therefore, in this application, the inventors have analyzed and studied the chemical composition of high-aluminum fly ash, and on this basis, used CaCl2·2H2O activation technology and hydrochloric acid to dissolve aluminum and gallium from fly ash from pulverized coal furnaces, thus finding a new way to extract aluminum and gallium from fly ash from pulverized coal furnaces, and thus proposed a series of protection schemes of this application.
[0020] In a first typical embodiment of the present application, a method for producing aluminum oxide and gallium chloride from fly ash is provided, the method comprising: a) mixing fly ash with a calcining agent to obtain a solid phase material; calcining the solid phase material to obtain clinker; b) soaking the clinker in a first hydrochloric acid solution, separating the solid and the liquid, and obtaining the impurity-removed clinker; soaking the impurity-removed clinker in a second hydrochloric acid solution, separating the solid and the liquid, and obtaining an eluate, wherein the eluate is aluminum chloride; c) adsorbing the eluate through a resin to obtain an effluent and an adsorption resin; d) washing the adsorption resin with a third hydrochloric acid to obtain gallium chloride; e) crystallizing the effluent to obtain aluminum chloride hexahydrate crystals; and calcining the aluminum chloride hexahydrate crystals to obtain aluminum oxide and hydrogen chloride gas.
[0021] By using the above method, aluminum oxide and gallium chloride can be separated from fly ash. The clinker is treated with hydrochloric acid, and aluminum and gallium elements are present in the form of ions in the dissolution solution. The aluminum ions and gallium ions in the dissolution solution are separated by resin. Gallium ions are adsorbed on the resin, and aluminum ions flow out with the effluent. After the adsorption resin adsorbed with gallium ions is eluted with hydrochloric acid, gallium ions are eluted from the resin, and gallium chloride is obtained. The gallium chloride is the gallium electrolytic stock solution, and high-purity gallium or gallium-containing compounds are prepared from the gallium electrolytic stock solution in the subsequent process.
[0022] The main ions present in the effluent are aluminum ions and chloride ions. By crystallizing the effluent, aluminum chloride hexahydrate crystals with higher purity can be obtained. The crystallization process of aluminum chloride is simple and easy to control. Compared with other aluminum compounds such as aluminum sulfate and aluminum nitrate, it is easier to form a crystal structure. The aluminum sulfate crystallization process is prone to colloidal phenomena, and the thermal decomposition of aluminum nitrate is dangerous. The thermal decomposition products of both are highly toxic, and the recovery process is complicated, requiring a catalyst to improve the reaction efficiency, and the processing is difficult. Further, aluminum chloride hexahydrate crystals are burned to obtain aluminum oxide and hydrogen chloride gas with higher purity. Hydrogen chloride gas is simple to recover, is highly soluble in water, and can be further dissolved in water to form hydrochloric acid, thereby recycling and saving production costs. For the recovery of hydrogen chloride gas, the cost is low and the efficiency is high. Compared with sulfur dioxide and sulfur trioxide produced by roasting aluminum sulfate, and nitrogen oxides produced by roasting aluminum nitrate, the cost and difficulty of recovery are significantly reduced.
[0023] Moreover, the above method reduces the desiliconization step that must be performed in the prior art. In the above method, hydrochloric acid cannot dissolve silicon oxide in fly ash. The filtration process after dissolution removes most of the silicon oxide solids. During the preparation process, only a trace amount of silicon oxide enters the solution, and part of it is removed by crystallization. The obtained product can meet the product requirements, and the mass percentage of silicon oxide in the product is less than 0.02%.
[0024] Some aluminum oxide and gallium oxide in fly ash exist in the form of Al-O-Si and Ga-O-Si, which are chemically stable. The above method activates the aluminum oxide or gallium oxide through a calcining agent to destroy the Al-O or O-Si, Ga-O bonds, thereby increasing the activity of the aluminum oxide or gallium oxide and making it easier to be dissolved by hydrochloric acid.
[0025] In the method of the present application, hydrochloric acid can be recycled, which greatly reduces the cost of raw materials for production. In addition, for the aluminum chloride intermediate product of aluminum oxide, high-purity aluminum chloride crystals can be obtained after simple crystallization, and high-purity aluminum oxide products can be further obtained, thereby improving the purity of aluminum, reducing the process and cost required for subsequent purification, and reducing industrial production costs.
[0026] It should be noted that the first hydrochloric acid solution, the second hydrochloric acid solution, the third hydrochloric acid solution and the fourth hydrochloric acid solution in the present application all refer to hydrochloric acid solutions, and the distinction between "first", "second", "third" and "fourth" is only to distinguish the types of hydrochloric acid solutions.
[0027] In a preferred embodiment, in a), the calcining agent includes CaCl2·2H2O; preferably, the mass ratio of fly ash to calcining agent is 0.3-2:1, more preferably 0.8-1.2:1; preferably, the calcination temperature of the solid phase material is 600-1200°C, more preferably 900-1100°C; preferably, the calcination time of the solid phase material is 1.5-5h, more preferably 3-4h.
[0028] Compared with anhydrous calcium chloride, CaCl2·2H2O has lower cost, and anhydrous calcium chloride easily absorbs water, making it difficult to meet the requirements of a calcining agent when used.
[0029] In a preferred embodiment, in b), the mass content of the first hydrochloric acid solution is 0.2% to 30%, preferably 0.5% to 5.0%; preferably, the volume mass ratio of the first hydrochloric acid solution to the clinker is 3 to 10 mL: 1 g, more preferably 4 to 6 mL: 1 g; preferably, the soaking time of the clinker is 0.5 to 3 h, more preferably 1 to 2 h.
[0030] The first hydrochloric acid solution can be used to remove impurities such as calcium and magnesium in the clinker, thereby reducing the subsequent impact of such impurities on the purity of aluminum and gallium products.
[0031] In a preferred embodiment, in b), the mass content of the second hydrochloric acid is 15% to 31%, preferably 20% to 29%; preferably, the volume mass ratio of the second hydrochloric acid solution to the de-impurity clinker is 3 to 8 mL: 1 g, more preferably 4 to 5 mL: 1 g; preferably, the soaking time of the de-impurity clinker is 0.5 to 5 h, more preferably 1 to 2 h; preferably, the soaking temperature of the de-impurity clinker is 40 to 160°C, more preferably 50 to 70°C.
[0032] The first hydrochloric acid used above is used to remove excess Ca impurities, and the second hydrochloric acid is used to dissolve aluminum oxide and gallium oxide.
[0033] In a preferred embodiment, in c), the resin includes a quaternary ammonium anion exchange resin; preferably, the flow rate of the eluate in the resin is 1.5 to 5.0 BV / h, more preferably 2.0 to 3.5 BV / h; preferably, the iron ion concentration in the eluate is 200 to 320 g / L, more preferably 250 to 300 g / L.
[0034] When the dissolution flows through the resin, the gallium, iron and other elements in the dissolution are easily adsorbed on the resin. The resin adsorbing a large amount of such elements is the adsorption resin; while the aluminum ion has a weak affinity with the resin and exists in large quantities in the effluent flowing through the resin. BV is the volume ratio of the dissolution to the resin. The concentration of iron ions in the dissolution is adjusted by concentration and other methods, so that iron and gallium can be better separated in the orderly resin adsorption.
[0035] In a preferred embodiment, in d), the mass content of the third hydrochloric acid is 0.5%-5%; preferably, after washing the adsorption resin with the third hydrochloric acid, sodium hydroxide is added to the eluent, and a gallium-rich solution is obtained after filtration, and a fourth hydrochloric acid solution is added to adjust the pH to obtain gallium chloride; preferably, the added sodium hydroxide is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 3-8 mol / L, more preferably 5-6 mol / L; preferably, after adding sodium hydroxide, the concentration is maintained for 0.5-4h to obtain a gallium-rich solution, more preferably 1-2h; preferably, the temperature after adding sodium hydroxide is 40-90°C, more preferably 60-80°C; preferably, the pH is adjusted to 1-3 to obtain gallium chloride, more preferably 1.8-2.2.
[0036] The third solution can be used to elute gallium, iron and other ions on the adsorption resin to obtain an eluent. By adding an alkaline reagent such as sodium hydroxide to the eluent, the iron ions can be precipitated in the form of solids such as iron hydroxide, thereby separating gallium from iron and obtaining a solution with a high purity of gallium ions. Further adding a hydrochloric acid solution to adjust the pH, gallium chloride can be obtained. The gallium in the stock solution has a high purity and less impurities, and can be used for the production of single-element gallium.
[0037] In a preferred embodiment, in e), crystallization includes evaporative crystallization; preferably, the temperature of evaporative crystallization is 105-150°C, more preferably 110-120°C; preferably, the roasting temperature of aluminum chloride hexahydrate crystals is 900-1150°C, more preferably 1000-1050°C; preferably, the roasting time of aluminum chloride hexahydrate crystals is 2-5h, more preferably 2.5-3h.
[0038] Aluminum chloride hexahydrate is easy to crystallize, and high-purity aluminum chloride hexahydrate crystals can be obtained through common methods such as evaporation crystallization. Similar aluminum-containing compounds, such as aluminum sulfate, are very easy to gel during crystallization, which makes it very difficult to control the crystallization process. In addition, the gelled aluminum sulfate contains other impurities and cannot form high-purity crystals, which easily leads to low purity of the subsequent aluminum oxide.
[0039] In a preferred embodiment, in d), after adding the fourth hydrochloric acid solution to adjust the pH, an organic extractant is added for extraction and separation to obtain an organic phase; and the organic phase is back-extracted and separated using an aqueous back-extractant to obtain gallium chloride.
[0040] In a preferred embodiment, the organic extractant includes an extractant and a diluent, the extractant includes tributyl phosphate and di(2-ethylhexyl)phosphoric acid, and the diluent includes sulfonated kerosene; the volume ratio of tributyl phosphate to di(2-ethylhexyl)phosphoric acid is 1 to 6:1, preferably 2 to 3:1; the volume ratio of the extractant to the diluent is 0.5 to 2:1; preferably, the extraction temperature is 20 to 30°C; preferably, the extraction time is 10 to 60 min.
[0041] In a preferred embodiment, before back extraction, the organic phase is washed with a fifth hydrochloric acid solution, the mass content of the fifth hydrochloric acid solution is 25%-36%, preferably 30%-36%; preferably, the volume ratio of the fifth hydrochloric acid to the organic phase is 2:1; preferably, the washing time of the fifth hydrochloric acid solution is 10-30 min; preferably, the aqueous back extraction agent includes a sixth hydrochloric acid solution, the mass content of the sixth hydrochloric acid solution is 0.8%-5%, more preferably 1%-3%; preferably, the back extraction temperature is 20-30°C; preferably, the back extraction time is 10-60 min, more preferably 20-30 min; preferably, after back extraction with an aqueous back extraction agent, the solution is concentrated and then separated to obtain gallium chloride.
[0042] By adjusting pH, extracting and stripping, the purity of gallium in the gallium-rich solution can be further improved, and finally high-purity gallium chloride can be obtained. Since gallium ions have a high solubility in inorganic acid (hydrochloric acid), separation after concentration can make more gallium ions dissolve in the aqueous back-extractant, reduce the residual gallium ions in the organic phase, and thus improve the yield of gallium chloride.
[0043] The beneficial effects of the present application will be further explained in detail below in conjunction with specific embodiments.
[0044] Example 1
[0045] Take 10g of fly ash from a pulverized coal furnace and 10g of CaCl2, mix them evenly to obtain a solid phase material, roast it at 1100℃ for 3 hours, cool it naturally, and react the clinker with hydrochloric acid (3%) at a solid-liquid ratio of 1:4 for 1 hour. The clinker after impurity removal is transferred to a reactor, and hydrochloric acid (26%) solution is added for dissolution. The dissolution temperature is 60℃, the time is 2 hours, and the liquid-solid ratio is 4:1. The reaction process is carried out in a rotary reactor. After the reaction is completed, liquid-solid separation and washing are carried out. The dissolution liquid passes through the ion exchange resin at 3.0BV / h.
[0046] The adsorption resin saturated with adsorption is washed with dilute hydrochloric acid (1%) to obtain chlorides such as ferric chloride and gallium chloride, which are eluted and concentrated. 6 mol / L sodium hydroxide solution is added to adjust the pH to 11, the temperature is controlled at 60°C, the time is 1 hour, and the gallium-rich solution is obtained after filtration, and then the pH is adjusted to 1.8 with hydrochloric acid to obtain a gallium-containing solution. The gallium-containing solution uses an extractant: tributyl phosphate (TBP): di(2-ethylhexyl) phosphoric acid (D2EHPA) = 2:1, sulfonated kerosene: extractant = 1:1. The gallium-containing solution and the extractant are reacted in a volume ratio of 1:2. During the extraction, the water bath thermostat shaker controls the temperature: 25°C, the time: 20min, and after the reaction is completed, the organic phase is separated and washed, the washing hydrochloric acid concentration is 36%, and the washing is 20min. Then, the stripping agent and the extracting liquid are stripped in a volume ratio of 2:1, and dilute hydrochloric acid (1%) is used as the stripping agent. During the stripping, the water bath thermostat shaker controls the temperature at 25°C, the time: 20min, and gallium chloride is obtained.
[0047] After impurities are removed, the dissolution solution is evaporated and crystallized to obtain aluminum chloride hexahydrate crystals. The aluminum chloride hexahydrate crystals are calcined at 1000°C for 3 hours to obtain aluminum oxide. The hydrogen chloride gas is recovered and then further dissolved and recycled. See the reaction flow chart Figure 1 Gallium chloride and aluminum oxide were tested, and the experimental data are shown in Table 1. In this application and the prior art, the data related to gallium dissolution are expressed using gallium oxide. The detection method used in this application adopts the method in GB / T 6609.1-2018 standard.
[0048] Table 1 Experimental results
[0049]
[0050] Example 2
[0051] Take 10g of fly ash from a pulverized coal furnace and 10g of CaCl2, mix them evenly to obtain a solid phase material, roast it at 1000℃ for 4 hours, cool it naturally, and react the clinker with hydrochloric acid (3%) at a solid-liquid ratio of 1:4 for 1 hour. The clinker after impurity removal is transferred to a reactor, and hydrochloric acid (26%) solution is added for dissolution. The dissolution temperature is 60℃, the time is 2 hours, and the liquid-solid ratio is 4:1. The reaction process is carried out in a rotary reactor. After the reaction is completed, liquid-solid separation and washing are carried out. The dissolution liquid passes through the ion exchange resin at 3.0BV / h.
[0052] The adsorption resin saturated with adsorption is washed with dilute hydrochloric acid (1%) to obtain chlorides such as ferric chloride and gallium chloride, which are eluted and concentrated. 5 mol / L sodium hydroxide solution is added to adjust the pH to 11, the temperature is controlled at 60°C, the time is 1 hour, and the gallium-rich solution is obtained after filtration, and then the pH is adjusted to 1.8 with hydrochloric acid to obtain a gallium-containing solution. The gallium-containing solution uses an extractant: tributyl phosphate (TBP): di(2-ethylhexyl) phosphoric acid (D2EHPA) = 2:1, sulfonated kerosene: extractant = 1:1. The gallium-containing solution and the extractant are reacted in a volume ratio of 1:2. During the extraction, the water bath thermostat shaker controls the temperature: 25°C, the time: 20min, after the reaction is completed, the organic phase is separated and washed, the washing hydrochloric acid concentration is 36%, the washing is 20min, and then the stripping agent and the extracting liquid are stripped in a volume ratio of 2:1, dilute hydrochloric acid (1%) is used as the stripping agent, and the water bath thermostat shaker controls the temperature at 25°C during the stripping, the time: 20min, and gallium chloride is obtained.
[0053] After impurities are removed, the dissolving liquid is evaporated and crystallized to obtain aluminum chloride hexahydrate crystals. Aluminum chloride hexahydrate is calcined at 1000°C for 3 hours to obtain aluminum oxide, and the hydrogen chloride gas is recovered and then further dissolved and recycled. Gallium chloride and aluminum oxide are tested, and the experimental data are shown in Table 2.
[0054] Table 2
[0055]
[0056] Example 3
[0057] Take 10g of fly ash from a pulverized coal furnace and 10g of CaCl2, mix them evenly to obtain a solid phase material, roast it at 1100℃ for 3 hours, cool it naturally, and react the clinker with hydrochloric acid (3%) at a solid-liquid ratio of 1:4 for 1 hour. The clinker after impurity removal is transferred to a reactor, and hydrochloric acid (26%) solution is added for dissolution. The dissolution temperature is 60℃, the time is 2 hours, and the liquid-solid ratio is 4:1. The reaction process is carried out in a rotary reactor. After the reaction is completed, liquid-solid separation and washing are carried out. The dissolution liquid passes through the ion exchange resin at 3.0BV / h.
[0058] The adsorption resin saturated with adsorption is washed with dilute hydrochloric acid (1%) to obtain chlorides such as ferric chloride and gallium chloride, which are eluted and concentrated. 6 mol / L sodium hydroxide solution is added to adjust the pH to 11, the temperature is controlled at 60°C, the time is 1 hour, and the gallium-rich solution is obtained after filtration, and then the pH is adjusted to 2.2 with hydrochloric acid to obtain a gallium-containing solution. The gallium-containing solution uses an extractant: tributyl phosphate (TBP): di(2-ethylhexyl) phosphoric acid (D2EHPA) = 3:1, sulfonated kerosene: extractant = 1:1. The gallium-containing solution and the extractant are reacted in a volume ratio of 1:2. During the extraction, the water bath thermostat shaker controls the temperature: 25°C, the time: 20min, after the reaction is completed, the organic phase is separated and washed, the washing hydrochloric acid concentration is 30%, the washing is 30min, and then the stripping agent and the extracting liquid are stripped with a volume ratio of 2:1, dilute hydrochloric acid (1%) as the stripping agent, and the water bath thermostat shaker controls the temperature at 25°C during the stripping, the time: 20min, and gallium chloride is obtained.
[0059] After impurities are removed, the dissolving liquid is evaporated and crystallized to obtain aluminum chloride hexahydrate crystals. Aluminum chloride hexahydrate is calcined at 1000°C for 3 hours to obtain aluminum oxide, and the hydrogen chloride gas is recovered and then further dissolved and recycled. Gallium chloride and aluminum oxide are tested, and the experimental data are shown in Table 3.
[0060] Table 3
[0061]
[0062] Example 4
[0063] Take 10g of fly ash from a pulverized coal furnace and 10g of CaCl2, mix them evenly to obtain a solid phase material, roast it at 1100℃ for 3 hours, cool it naturally, and react the clinker with hydrochloric acid (3%) at a solid-liquid ratio of 1:4 for 1 hour. The clinker after impurity removal is transferred to a reactor, and hydrochloric acid (26%) solution is added for dissolution. The dissolution temperature is 60℃, the time is 2 hours, and the liquid-solid ratio is 4:1. The reaction process is carried out in a rotary reactor. After the reaction is completed, liquid-solid separation and washing are carried out. The dissolution liquid passes through the ion exchange resin at 3.0BV / h.
[0064] The adsorption resin saturated with adsorption is washed with dilute hydrochloric acid (1%) to obtain chlorides such as ferric chloride and gallium chloride, which are eluted and concentrated. 6 mol / L sodium hydroxide solution is added to adjust the pH to 11, the temperature is controlled at 60°C, the time is 1 hour, and the gallium-rich solution is obtained after filtration, and then the pH is adjusted to 1.8 with hydrochloric acid to obtain a gallium-containing solution. The gallium-containing solution uses an extractant: tributyl phosphate (TBP): di(2-ethylhexyl) phosphoric acid (D2EHPA) = 3:1, sulfonated kerosene: extractant = 1:1. The gallium-containing solution and the extractant are reacted in a volume ratio of 1:2. During the extraction, the water bath thermostat shaker controls the temperature: 25°C, the time: 20min, after the reaction is completed, the organic phase is separated and washed, the washing hydrochloric acid concentration is 36%, the washing is 30min, and then the stripping agent and the extracting liquid are stripped in a volume ratio of 2:1, dilute hydrochloric acid (1%) is used as the stripping agent, and the water bath thermostat shaker controls the temperature at 25°C during the stripping, the time: 20min, and gallium chloride is obtained.
[0065] After impurities are removed, the dissolving liquid is evaporated and crystallized to obtain aluminum chloride hexahydrate crystals. Aluminum chloride hexahydrate is calcined at 1000°C for 3 hours to obtain aluminum oxide, and the hydrogen chloride gas is recovered and then further dissolved and recycled. Gallium chloride and aluminum oxide are tested, and the experimental data are shown in Table 4.
[0066] Table 4
[0067]
[0068] Comparative Example 1
[0069] Take 10g of fly ash from a pulverized coal furnace and 10g of CaCl2, mix them evenly to obtain a solid phase material, roast it at 500℃ for 3 hours, cool it naturally, and react the clinker with hydrochloric acid (3%) at a solid-liquid ratio of 1:4 for 1 hour. The clinker after impurity removal is transferred to a reactor, and hydrochloric acid (26%) solution is added for dissolution. The dissolution temperature is 60℃, the time is 0.3 hours, and the liquid-solid ratio is 4:1. The reaction process is carried out in a rotary reactor. After the reaction is completed, liquid-solid separation and washing are carried out. The dissolution liquid passes through the ion exchange resin at 3.0BV / h.
[0070] The adsorption resin saturated with adsorption is washed with dilute hydrochloric acid (1%) to obtain chlorides such as ferric chloride and gallium chloride, which are eluted and concentrated. 6 mol / L sodium hydroxide solution is added to adjust the pH to 11, the temperature is controlled at 60°C, the time is 1 hour, and the gallium-rich solution is obtained after filtration, and then the pH is adjusted to 1.8 with hydrochloric acid to obtain a gallium-containing solution. The gallium-containing solution uses an extractant: tributyl phosphate (TBP): di(2-ethylhexyl) phosphoric acid (D2EHPA) = 2:1, sulfonated kerosene: extractant = 1:1. The gallium-containing solution and the extractant are reacted in a volume ratio of 1:2. During the extraction, the water bath thermostat shaker controls the temperature: 25°C, the time: 20min, and after the reaction is completed, the organic phase is separated and washed, the washing hydrochloric acid concentration is 36%, and the washing is 10min. Then, the stripping agent and the extracting liquid are stripped in a volume ratio of 2:1, and dilute hydrochloric acid (1%) is used as the stripping agent. During the stripping, the water bath thermostat shaker controls the temperature at 25°C, the time: 20min, and gallium chloride is obtained.
[0071] After impurities are removed, the dissolution solution is evaporated and crystallized to obtain aluminum chloride hexahydrate crystals. Aluminum chloride hexahydrate is calcined at 1000°C for 3 hours to obtain aluminum oxide, and the hydrogen chloride gas is recovered and then further dissolved and recycled. Gallium chloride and aluminum oxide are tested, and the experimental data are shown in Table 5.
[0072] Table 5
[0073]
[0074] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects: a variety of different hydrochloric acid solutions are used to dissolve and purify aluminum and gallium in the fly ash of the pulverized coal furnace, and high-purity aluminum oxide and gallium chloride are obtained, which finds a new way to extract aluminum and gallium elements from the fly ash of the pulverized coal furnace. The production process is simple, the cost is low, and the product obtained is of high purity.
[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for producing aluminum oxide and gallium chloride from fly ash, characterized in that: The method comprises: a) mixing fly ash with a calcining agent to obtain a solid phase material; and calcining the solid phase material to obtain clinker; b) soaking the clinker in a first hydrochloric acid solution to separate the solid from the liquid to obtain the impurity-removed clinker; soaking the impurity-removed clinker in a second hydrochloric acid solution to separate the solid from the liquid and obtain a dissolving solution; c) the eluate is adsorbed by a resin to obtain an effluent and an adsorption resin, wherein the effluent is aluminum chloride; d) washing the adsorption resin with a third hydrochloric acid to obtain the gallium chloride; e) crystallizing the effluent to obtain aluminum chloride hexahydrate crystals; and calcining the aluminum chloride hexahydrate crystals to obtain aluminum oxide and hydrogen chloride gas.
2. The method according to claim 1, characterized in that In a), the calcining agent includes CaCl2·2H2O; Preferably, the mass ratio of the fly ash to the calcining agent is 0.3 to 2:1, more preferably 0.8 to 1.2:1; Preferably, the calcination temperature of the solid phase material is 600-1200°C, more preferably 900-1100°C; Preferably, the calcination time of the solid phase material is 1.5 to 5 hours, more preferably 3 to 4 hours.
3. The method according to claim 1, characterized in that In b), the mass content of the first hydrochloric acid solution is 0.2% to 30%, preferably 0.5% to 5.0%; Preferably, the volume mass ratio of the first hydrochloric acid solution to the clinker is 3-10 mL:1 g, more preferably 4-6 mL:1 g; Preferably, the soaking time of the clinker is 0.5 to 3 hours, more preferably 1 to 2 hours.
4. The method according to claim 1, characterized in that: In b), the mass content of the second hydrochloric acid is 15% to 31%, preferably 20% to 29%; Preferably, the volume mass ratio of the second hydrochloric acid solution to the impurity-removed clinker is 3-8 mL:1 g, more preferably 4-5 mL:1 g; Preferably, the soaking time of the impurity-removed clinker is 0.5 to 5 hours, more preferably 1 to 2 hours; Preferably, the temperature for soaking the impurity-removed clinker is 40-160°C, more preferably 50-70°C.
5. The method according to claim 1, characterized in that In c), the resin comprises a quaternary ammonium anion exchange resin; Preferably, the flow rate of the dissolving solution in the resin is 1.5 to 5.0 BV / h, more preferably 2.0 to 3.5 BV / h; Preferably, the iron ion concentration in the dissolution solution is 200-320 g / L, more preferably 250-300 g / L.
6. The method according to claim 1, characterized in that In said d), the mass content of said third hydrochloric acid is 0.5%-5%; Preferably, after washing the adsorption resin with the third hydrochloric acid, sodium hydroxide is added to the eluate, and a gallium-rich solution is obtained after filtration, and a fourth hydrochloric acid solution is added to adjust the pH to obtain the gallium chloride; Preferably, the added sodium hydroxide is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 3 to 8 mol / L, more preferably 5 to 6 mol / L; Preferably, the sodium hydroxide is added and maintained for 0.5 to 4 hours to obtain the gallium-rich solution, more preferably for 1 to 2 hours; Preferably, the temperature after adding the sodium hydroxide is 40 to 90° C., more preferably 60 to 80° C.; Preferably, the pH is adjusted to 1-3 to obtain the gallium chloride, more preferably 1.8-2.
2.
7. The method according to claim 1, characterized in that In said e), said crystallization comprises evaporative crystallization; Preferably, the temperature of the evaporation crystallization is 105-150°C, more preferably 110-120°C; Preferably, the calcination temperature of the aluminum chloride hexahydrate crystals is 900-1150° C., more preferably 1000-1050° C.; Preferably, the calcination time of the aluminum chloride hexahydrate crystals is 2 to 5 hours, more preferably 2.5 to 3 hours.
8. The method according to claim 6, characterized in that In said d), after adding said fourth hydrochloric acid solution to adjust said pH, adding an organic extractant to perform extraction and liquid separation to obtain an organic phase; The organic phase is back-extracted and separated by using an aqueous back-extracting agent to obtain the gallium chloride.
9. The method according to claim 8, characterized in that The organic extractant comprises an extractant and a diluent, the extractant comprises tributyl phosphate and di(2-ethylhexyl)phosphoric acid, and the diluent comprises sulfonated kerosene; The volume ratio of the tributyl phosphate to the di(2-ethylhexyl)phosphoric acid is 1 to 6:1, preferably 2 to 3:1; The volume ratio of the extractant to the diluent is 0.5 to 2:1; Preferably, the extraction temperature is 20-30°C; Preferably, the extraction time is 10 to 60 minutes.
10. The method according to claim 8, characterized in that Before the stripping, the organic phase is washed with a fifth hydrochloric acid solution, wherein the mass content of the fifth hydrochloric acid solution is 25%-36%, preferably 30%-36%; Preferably, the volume ratio of the fifth hydrochloric acid to the organic phase is 2:1; Preferably, the washing time of the fifth hydrochloric acid solution is 10 to 30 minutes; Preferably, the aqueous back-extraction agent comprises a sixth hydrochloric acid solution, and the mass content of the sixth hydrochloric acid solution is 0.8%-5%, more preferably 1%-3%; Preferably, the stripping temperature is 20-30°C; Preferably, the stripping time is 10 to 60 min, more preferably 20 to 30 min; Preferably, the stripping is performed using the aqueous back-extraction agent, followed by concentration and then liquid separation to obtain the gallium chloride.
